The association between interoception and psychopathic traits - Gao, Yu; Murphy, Amanda; Kofler, Liat (Frontiers in Psychology, 2026)
IntroductionPsychopathic traits are characterized by pervasive emotional deficits, including diminished empathy and remorse, heightened impulsivity, and antisocial behavior. Prior work has suggested that these traits may be partly shaped by physiological abnormality, although their associations with interoception—defined as the sensitivity to and awareness of internal bodily signals—has been inconsistent and understudied. The present study aimed to clarify the nature of emotional impairments in psychopathy by examining potential interoceptive abnormalities during a social stress task in a non-incarcerated, non-clinical sample.MethodsOne hundred and fourteen participants (62% women; mean age = 22) from a local college and the surrounding community self-reported psychopathic traits, and their skin conductance level (SCL) was recorded while they experienced social exclusion during a computerized task. Following the task, they reported bodily sensations as an index of interoceptive sensibility. Based on the correspondence between subjective sensations and physiological responses, three interoceptive profiles were identified: an under-reporting group (greater SCL relative to reported sensations), an over-reporting group (lower SCL relative to reported sensations), and a control group (broad match between SCL and reported sensations).ResultsSelf-Centered Impulsivity and Coldheartedness were positively and negatively associated, respectively, with interoceptive sensibility. In addition, the over-reporting group scored higher on Self-Centered Impulsivity than the other two groups.DiscussionFindings suggest that interoceptive disturbances may be particularly characteristic of the impulsive and antisocial behavioral dimension of psychopathy, which is associated with a high tendency to hyper-vigilance and over-report of bodily sensations.